Propolis residue inclusion in the diet affects digestive enzyme activity in broiler chickens - Cristiane Regina do Amaral Duarte; Cinthia Eyng; Alice Eiko Murakami; Mayra Diaz Vargas; Ricardo Vianna Nunes (Semina: Ciências Agrárias, 2017)
This study investigated the effects of the inclusion of solid propolis residue (PR) from alcoholic propolis extraction in the diets of broiler chickens from 1 to 21-d of age on their performance, intestinal morphology, and digestive enzyme activity. 405 male chicks were distributed in a completely randomized design with five treatments (inclusion of 0, 1, 2, 3 and 4% PR in the diets), and three replications with 27 birds each. The birds were fed experimental diets from 1 to 21-d of age and basal diet from 22 to 42-d of age. Feed intake (from 1 to 21-d and 1 to 42-d of age) decreased linearly with increasing levels of PR inclusion (P < 0.05). Dietary inclusion of PR did not affect intestinal morphology at 7 and 21-d of age (P > 0.05). Pancreatic amylase activity presented a quadratic response at 7 and 21-d of age, with its lowest activity estimated at 2.45 and 1.91% PR inclusion, respectively. At 7-d of age, trypsin activity decreased linearly, whereas chymotrypsin activity varied quadratically, with its activity estimated at 2.06% PR inclusion. Intestinal maltase activity varied quadratically with lowest activity predicted at 1.57% PR inclusion at 21-d of age. The dietary inclusion of solid propolis residue of propolis decreases feed intake in broilers and modulates their intestinal and pancreatic enzyme activity.